Transmission disequilibrium analysis of whole genome data in childhood-onset systemic lupus erythematosus - Vazzana, Kathleen M.; Musolf, Anthony M.; Bailey-Wilson, Joan E.; Hiraki, Linda T.; Silverman, Earl D.; Scott, Christiaan; Dalgard, Clifton L.; Hasni, Sarfaraz; Deng, Zuoming; Kaplan, Mariana J.; Lewandowski, Laura B. (Genes and immunity, 2023)
Childhood-onset systemic lupus erythematosus (cSLE) patients are unique, with hallmarks of Mendelian disorders (early-onset and severe disease) and thus are an ideal population for genetic investigation of SLE. In this study, we use the transmission disequilibrium test (TDT), a family-based genetic association analysis that employs robust methodology, to analyze whole genome sequencing data. We aim to identify novel genetic associations in an ancestrally diverse, international cSLE cohort. Forty-two cSLE patients and 84 unaffected parents from 3 countries underwent whole genome sequencing. First, we performed TDT with single nucleotide variant (SNV)-based (common variants) using PLINK 1.9, and gene-based (rare variants) analyses using Efficient and Parallelizable Association Container Toolbox (EPACTS) and rare variant TDT (rvTDT), which applies multiple gene-based burden tests adapted for TDT, including the burden of rare variants test. Applying the GWAS standard threshold (5.0 × 10 −8 ) to common variants, our SNV-based analysis did not return any genome-wide significant SNVs. The rare variant gene-based TDT analysis identified many novel genes significantly enriched in cSLE patients, including HNRNPUL2 , a DNA repair protein, and DNAH11 , a ciliary movement protein, among others. Our approach identifies several novel SLE susceptibility genes in an ancestrally diverse childhood-onset lupus cohort.